Common Transcriptomic Effects of Abatacept and Other DMARDs on Rheumatoid Arthritis Synovial Tissue - Triaille, Clement; Durez, Patrick; Sokolova, Tatiana; Tilman, Gaëlle; Méric de Bellefon, Laurent; Galant, Christine; Coulie, Pierre; Lauwerys, Bernard R.; Limaye, Nisha (Frontiers in Immunology, 2021)
Objectives Our goal was to assess for the histological and transcriptomic effects of Abatacept on RA synovia, and to compare them with previously published data from four other DMARDs: Tocilizumab, Rituximab, Methotrexate and Adalimumab. Methods Synovial tissue was obtained using ultrasound-guided biopsy from affected joints of 14 patients, before and 16 weeks after treatment with subcutaneous Abatacept 125mg weekly. Paraffin-sections were stained and scored for CD3+, CD20+ and CD68+ cell infiltration. Transcriptional profiling was performed using GeneChip Human Genome U133 Plus 2.0 arrays (Affymetrix), and analyzed on Genespring GX (Agilent). Pathway analyses were performed on Genespring GX, Metascape and EnrichR. Results Gene expression analysis identified 304 transcripts modulated by Abatacept in synovial tissue. Downregulated genes were significantly enriched for immune processes, strongly overlapping with our findings on other therapies. Data were pooled across these studies, revealing that genes downregulated by DMARDs are significantly enriched for both T cell and myeloid leukocyte activation pathways. Interestingly, DMARDs seem to have coordinate effects on the two pathways, with a stronger impact in good responders to therapy as compared to moderate and non-responders. Conclusion We provide evidence that the effects of five DMARDs on the RA synovium culminate in the same pathways. This confirms previous studies suggesting the existence of common mediators downstream of DMARDs, independent of their primary targets.